2006
DOI: 10.2114/jpa2.25.7
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and Subjective Responses to Low Relative Humidity

Abstract: In order to investigate the influence of low relative humidity, we measured saccharin clearance time (SCT), frequency of blinking, heart rate (HR), blood pressure, hydration state of skin, transepidermal water loss (TEWL), recovery sebum level and skin temperature as physiological responses. We asked subjects to judge thermal, dryness and comfort sensations as subjective responses using a rating scale. Sixteen non-smoking healthy male students were selected. The pre-room conditions were maintained at an air te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
61
2
4

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(72 citation statements)
references
References 12 publications
5
61
2
4
Order By: Relevance
“…There are relatively more studies on the effects of RH in the 5% to 30% range, and they have generally found skin effects as well, especially in people with pre-existing atopic eczema [12][13][14][15][16][17][18] . In particular, Wyon 19) and Nordstrom et al 20) described an improvement of dry symptoms and sick building syndrome after humidification, and Reinikainen et al 21) reported a decrease in symptoms of allergic reactions in office workers subsequent to an elevation in RH from 20% to 40% in the working environment.…”
Section: Discussionmentioning
confidence: 99%
“…There are relatively more studies on the effects of RH in the 5% to 30% range, and they have generally found skin effects as well, especially in people with pre-existing atopic eczema [12][13][14][15][16][17][18] . In particular, Wyon 19) and Nordstrom et al 20) described an improvement of dry symptoms and sick building syndrome after humidification, and Reinikainen et al 21) reported a decrease in symptoms of allergic reactions in office workers subsequent to an elevation in RH from 20% to 40% in the working environment.…”
Section: Discussionmentioning
confidence: 99%
“…Subjects in the study by Laviana et al (1988) indicated no significant changes in eye comfort for healthy eyes without contacts between 10% and 30% RH. In the study by Sunwoo et al (2006a) blink frequency was higher at 30% RH and 10% RH than it was at 50% RH, but they did not address whether visual acuity was affected by environmental conditions. Wyon et al (2006) conducted a thorough study using a mucus ferning test which indicated eyes were drier at 5% and 15% RH compared to 25% and 35% RH at room temperature, suggesting that RH greater than 15% is preferable.…”
Section: Eye Irritationmentioning
confidence: 93%
“…The focus of the literature review was to determine the effects of low humidity on healthy eyes (Laviana et al, 1988;McCulley et al, 2006;Sunwoo et al, 2006a;Wyon et al, 2006;Arciniega et al, 2011;Abusharha and Pearce, 2013), although several papers were located that addressed the effects of humidity on subjects with dry eyes (Mathers and Daley, 1996;Borchman et al, 2009;Arciniega et al, 2011;Galor et al, 2011;Tomlinson et al, 2013). In addition, the effects of contact lenses were not the main focus of this study, but have been studied by several researchers (Laviana et al, 1988;Tsutsumi and Tanabe, 2002).…”
Section: Eye Irritationmentioning
confidence: 99%
“…Decrease of barrier function is associated with diseases such as atopic dermatitis (AD), [1][2][3][4] which is characterized by skin dryness and intense itching. Impairment of skin barrier function may also be caused by sudden change of the weather 5,6) or contact with chemical agents such as cleansers. 7,8) Severe itching may reduce the quality of life (QOL) through induction of sleep disorders.…”
Section: Introductionmentioning
confidence: 99%